The Days and Nights of Zoo Elephants: Using Epidemiology to Better Understand Stereotypic Behavior of African Elephants (Loxodonta africana) and Asian Elephants (Elephas maximus) in North American Zoos - Greco, Brian J. (PLoS One, 2016)
Stereotypic behavior is an important indicator of compromised welfare. Zoo elephants are documented to perform stereotypic behavior, but the factors that contribute to performance have not been systematically assessed. We collected behavioral data on 89 elephants (47 African [Loxodonta africana], 42 Asian [Elephas maximus]) at 39 North American zoos during the summer and winter. Elephants were videoed for a median of 12 daytime hours per season. A subset of 32 elephants (19 African, 13 Asian) was also observed live for a median of 10.5 nighttime hours. Percentages of visible behavior scans were calculated from five minute instantaneous samples. Stereotypic behavior was the second most commonly performed behavior (after feeding), making up 15.5% of observations during the daytime and 24.8% at nighttime. Negative binomial regression models fitted with generalized estimating equations were used to determine which social, housing, management, life history, and demographic variables were associated with daytime and nighttime stereotypic behavior rates. Species was a significant risk factor in both models, with Asian elephants at greater risk (daytime: p<0.001, Risk Ratio = 4.087; nighttime: p<0.001, Risk Ratio = 8.015). For both species, spending time housed separately (p<0.001, Risk Ratio = 1.009), and having experienced inter-zoo transfers (p<0.001, Risk Ratio = 1.175), increased the risk of performing higher rates of stereotypy during the day, while spending more time with juvenile elephants (p<0.001, Risk Ratio = 0.985), and engaging with zoo staff reduced this risk (p = 0.018, Risk Ratio = 0.988). At night, spending more time in environments with both indoor and outdoor areas (p = 0.013, Risk Ratio = 0.987) and in larger social groups (p = 0.039, Risk Ratio = 0.752) corresponded with reduced risk of performing higher rates of stereotypy, while having experienced inter-zoo transfers (p = 0.033, Risk Ratio = 1.115) increased this risk. Overall, our results indicate that factors related to the social environment are most influential in predicting elephant stereotypic behavior rates.